Calvin and mission - Jacobus (Kobus) P. Labuschagne (HTS Teologiese Studies/Theological Studies, 2009)
It has often been stated or implied that John Calvin and the Reformers in general were indifferent to or even against mission. The aim of this study is to point out that this understanding is not a true version of the facts. A thorough examination of the theology and actions of John Calvin, evaluated against the background of his times and world, reveals that he was firmly committed to spreading the Gospel of Jesus Christ, the Lord. Also the theological insights of Calvin and the Reformers not only provided the crucial theological basis to support the future massive missionary expansion of Protestant churches, but necessitate for all times Church mission as a sure consequence of their theology. Calvin’s theology can indeed be described as an ‘essentially missionary theology’. In the heart of Calvin’s theological thinking clearly features the doctrine of justifi cation – because medieval man’s concern for salvation needed to be answered.